An investigation of the sources, moderators, and psychological symptoms of stress among audit seniors* - HASKINS, MARK E.; BAGLIONI, A.J.; COOPER, CARY L. (Contemporary Accounting Research, 1990)
Abstract. One purpose of this study is to identify major sources of stress for audit seniors. Fifty‐nine different job‐related stressors are identified and investigated. Statistical evidence of increased dysfunctional psychological symptoms associated with increases in the presence of certain stressors is provided. In addition, four stress models that incorporate job stressors, personality types, coping behaviors, and psychological symptoms are investigated. Two mediating‐effects models were found to portray suitably the relationships among these items. Résumé. Les auteurs ont entre autres pour but de déterminer les principales sources de stress chez les chefs de mission. Cinquante‐neuf éléments inducteurs de stress différents liés au travail sont identifiés et analysés. L'analyse statistique démontre que les symptômes psychologiques dysfonctionnels augmentent avec la présence accrue de certains inducteurs de stress. Les auteurs analysent en outre quatre modèles de stress faisant intervenir des inducteurs de stress dans le travail, des types de personnalité, des comportements face aux difficultés et des symptômes psychologiques. Ils en viennent à la conclusion que deux modèles d'effets médiateurs illustrent de façon appropriée les relations entre ces éléments.